New directions in the sociology of global development - Buttel, Frederick H.; McMichael, Philip (Amsterdam ; London : Elsevier JAI, 2005)
Why is global development so unequal in its social impact? How are global relations represented in local developments, and vice versa? What role do social movements play in shaping global development? These are some of the questions animating this state-of-the-art collection of essays. Subdivided into sections posing research, policy, and strategic questions regarding contemporary social change, this volume brings together scholars well-known for challenging conventional wisdoms in the sociology of global development. In exploring development, these chapters range across the global North and South, economic sectors, policy scales, state/civil society relations, social models, and changing compositional and contextual dimensions of capitalism. Authors introduce conceptual innovations regarding the spatial boundaries of development, sovereignty and the politics of globalization, food regime analysis, recompositions of rural activity, the question of the national bourgeoisies role in the developing world, the health dimensions of food and farming, and the salience of regional governance in sustainable development. Methodologically, this collection breaks new ground with essays reinterpreting commodity chain analysis, accounting for the impoverishing impact of resource extraction, incorporating social movements into the analysis of development, and historically specifying contemporary trends in global development.
Title from PDF t.p. (viewed Jan. 20, 2010).
Includes bibliographical references.
Description based on print version record.
Keywords: Economic development -- Sociological aspects -- Congresses; Globalization -- Social aspects -- Congresses; Globalization; Development studies; Social Science -- Human Geography